Marine Bryozoans from the Northern Pacific Coast of Costa Rica - Beatriz Antillón-Obando; Jorge Cortés; Jeffrey A. Sibaja-Cordero (Diversity)
Although diverse and abundant, the phylum Bryozoa has been the subject of few studies in Costa Rica. Nearly 50 years have passed since Banta and Carson identified, described, and published twenty-four bryozoan species, including scanning electron microscope (SEM) images. To expand the knowledge of bryozoan diversity in the region, we sampled shallow coastal waters along the northern Pacific coast of Costa Rica and extracted tissue for DNA barcoding using the mitochondrial COI marker. Photographs of living specimens and SEM images were taken for morphological identification. We identified fifteen individuals belonging to nine bryozoan species from the orders Cyclostomatida and Cheilostomatida. Five of these species represent new records for Costa Rica (Savignyella lafontii, Bugula neritina, Watersipora arcuata, Smittipora levinseni, and Biflustra tenuis), while the remaining four (Disporella sp., Parasmittina crosslandi, Cigclisula sp., and Biflustra sp.) had been previously reported.